CP 2022
DOI: 10.12788/cp.0309
|View full text |Cite
|
Sign up to set email alerts
|

Psychedelics for treating psychiatric disorders: Are they safe?

Abstract: P sychedelics are a class of substances known to produce alterations in consciousness and perception. In the last 2 decades, psychedelic research has garnered increasing attention from scientists, therapists, entrepreneurs, and the public. While many of these compounds remain illegal in the United States and in many parts of the world (Box, 1 page 16), a recent resurrection of psychedelic research has motivated the FDA to designate multiple psychedelic compounds as "breakthrough therapies," thereby expediting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The most common adverse effects include anxiety, dysphoria, fear, confusion, increased blood pressure and heart rate, headache, nausea, fatigue, and dizziness which are typically dose-dependent and regarded as well-tolerated. Specific adverse effects of illusions (LSD), dissociation and sedation (ketamine), muscle tightening and jaw clenching (MDMA), and emesis (ayahuasca) are more compound specific, and similarly regarded as well-tolerated or essential to the therapeutic effect ( 67 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most common adverse effects include anxiety, dysphoria, fear, confusion, increased blood pressure and heart rate, headache, nausea, fatigue, and dizziness which are typically dose-dependent and regarded as well-tolerated. Specific adverse effects of illusions (LSD), dissociation and sedation (ketamine), muscle tightening and jaw clenching (MDMA), and emesis (ayahuasca) are more compound specific, and similarly regarded as well-tolerated or essential to the therapeutic effect ( 67 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, serotonin 5-HT2A agonists like psilocybin are relatively safe substances pharmacologically (Nichols, 2016). However, due to their mind-altering capabilities, risks incurred with psychedelics are predominantly psychological (Anderson, Danforth, & Grob, 2020;Nichols, 2016;Thakur, 2022). For instance, psychedelics appear to increase suggestibility and affective instability (Anderson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Goodwin et al (2022) found psilocybin dosage to dose-dependently predict suicidality and self-harm. As such, how psychological safety can be ensured during psilocybin-assisted therapy has yet to be fully illuminated (Thakur, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ketamine and Esketamine are both NMDA antagonists. 3 The therapeutic benefits of psychedelics are believed to arise from their capacity to induce significant alterations in consciousness, resulting in enduring changes in perspective and behavior. These substances seem to facilitate the brain's ability to create new neural connections (neuroplasticity), which can be advantageous for individuals with inflexible thought patterns linked to various mental health conditions.…”
Section: Introductionmentioning
confidence: 99%